Extração de areia: impactos socioambientais no município de Vigia de Nazaré - PA - SANTOS, Thaysa Danniela Siqueira dos (2024)
Sand extraction becomes an environmental problem from the moment it becomes essential for the production of concrete for civil, industrial and other construction. The market dynamics with the construction of houses and skyscrapers make this resource a base to be constantly explored in the economic line, common to other minerals, it has legislative follow-ups to be followed because it is categorized as a potentially polluting activity, however its disorderly extraction causes serious environmental and social impacts around the region, which gradually feels the harmful consequences in their daily lives. This work aims to analyze how the landscape in the villages of Acapú and São Cristóvão are affected by environmental management in the activities of mineral extraction of sand in the year 2023 in the municipality of Vigia de Nazaré- PA. Located in the coastal zone of the state of Pará, it has reserves and outcrops of this natural resource within its geographic space, which is constantly explored. The intention is to determine the position of the Municipal Department of the Environment on the case, since it is responsible for the environmental licensing process and inspection of the deposits in relation to this discussion. To develop the study, bibliographical research and field research were carried out. As a result, the research identified serious socio-environmental impacts that underlie the commercialization of sand, such as soil exposure, loss of local biodiversity, silting of streams and the spread of diseases resulting from the creation of lakes due to the removal of the ore. In response, SEMMA currently does not have any project to reverse the impacts and is experiencing complications regarding inspections.